AI Based Recruitment in Libya - Ebtesam Taktek (Aljameai, 2026)
AbstractArtificial intelligence (AI) has increasingly transformed organizational recruitment practices by supporting decision-making, improving efficiency, and enhancing candidate selection processes. This study investigates perceptions and acceptance of AI-based e-recruitment systems within organizational and higher education contexts in Libya. A quantitative research approach was employed using a structured questionnaire administered to 60 respondents from universities, higher education institutes, and business organizations.The findings indicate a generally positive attitude toward AI-supported recruitment, particularly regarding decision accuracy, reduced recruitment time, and improved selection effectiveness. However, respondents expressed reservations toward fully automated recruitment processes and emphasized the continued importance of human involvement in hiring decisions.The results suggest that hybrid recruitment models, combining AI-driven tools with human judgment, are perceived as the most appropriate approach for organizational decision-making. This study contributes to the information systems and organizational sciences literature by providing empirical insights into AI adoption in recruitment and its implications for organizational effectiveness and decision support.  المستخلص: يشهد الذكاء الاصطناعي (AI) تطورًا متزايدًا أسهم بشكل ملحوظ في تحويل إجراءات التوظيف داخل المؤسسات، من خلال دعمه لعمليات اتخاذ القرار، وتحسين الكفاءة، وتعزيز عمليات اختيار المرشحين. تهدف هذه الدراسة إلى استكشاف الانطباعات ومدى قبول أنظمة التوظيف الإلكتروني المعتمدة على الذكاء الاصطناعي في كلٍّ من المؤسسات التنظيمية ومؤسسات التعليم العالي في ليبيا. وقد اعتمدت الدراسة المنهج الكمي، وجُمعت البيانات باستخدام أداة جمع بيانات منظمة تم تطبيقها على عينة مؤلفة من 60 مشاركًا من الجامعات، ومؤسسات التعليم العالي، والمنظمات التجارية.تشير النتائج إلى وجود اتجاه إيجابي عام نحو التوظيف المدعوم بالذكاء الاصطناعي، لا سيما فيما يتعلق بدقة اتخاذ القرار، وتقليل الوقت اللازم لعمليات التوظيف، وتحسين فعالية اختيار المرشحين. ومع ذلك، عبّر المشاركون عن بعض التحفظات تجاه الاعتماد الكامل على الأتمتة في عمليات التوظيف، مؤكدين على الأهمية المستمرة للدور البشري في اتخاذ قرارات التعيين.وتُظهر النتائج أن نماذج التوظيف الهجينة، التي تجمع بين أدوات الذكاء الاصطناعي والحكم البشري، تُعد الخيار الأنسب لاتخاذ القرارات التنظيمية. وتسهم هذه الدراسة في إثراء أدبيات نظم المعلومات والعلوم التنظيمية من خلال تقديم رؤى تجريبية حول تبني الذكاء الاصطناعي في التوظيف وآثاره على الفاعلية التنظيمية ودعم القرار.